PENGARUH MEDIA PEMBELAJARAN ARTICULATE STORYLINE BERBASIS DEEP LEARNING TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS XI SMK TKM TEKNIK PURWOREJO TAHUN PELAJARAN 2025/2026 - Fina; Khabib Sholeh; Joko Purwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by unengaging learning practices resulting from conventional methods and a lack of innovation in instructional media. The purpose of this study was to determine the effect of the deep learning-based Articulate Storyline instructional media on the poetry-writing skills and learning interest of 11th-grade students at SMK TKM Teknik Purworejo. This study is a quantitative study using an experimental method with a nonequivalent control group design. The research sample consisted of the 11th-grade Electrical Power Installation class as the experimental group and the 11th-grade Machining class A as the control group. The author conducted data analysis prerequisite tests to determine whether the collected data were normally distributed, homogeneous, and whether there were any significant differences. The findings of this study indicate that there is an effect of the deep learning-based Articulate Storyline on students’ poetry writing skills, with a score difference of 15.68. The results show a significant difference in students’ poetry writing skills between the experimental group and the control group. The deep learning-based Articulate Storyline approach influenced students’ interest in learning, resulting in a 3.73% increase; therefore, this approach can enhance students’ poetry writing skills as well as their interest in learning poetry writing.